Implementasi Program Getol Beriman dalam Menanamkan Karakter Peduli Lingkungan di SDIT Qurrota Ayun Ponorogo - Susanti, Eka (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2022)
Abstract: GETOL BERIMAN (clean and comfortable toilet movement) is a program to inculcate a clean culture and care for the environment carried out at SDIT Qurrota A'yun Ponorogo in 2022, which contains seven habits when going to the bathroom that students must apply. This study aims to discuss the form and implementation of the GETOL BERIMAN program in instilling the character of caring for the environment in students. This type of research is a qualitative descriptive field research. The data sources of this research are all school residents, the environment and relevant school data. Data collection techniques through interviews, observation, and documentation. While the data analysis with data reduction, data presentation, and drawing conclusions. Based on the discussion, it can be concluded that: (1) The form of the GETOL BERIMAN program is in the form of seven habits contained in the GETOL BERIMAN book that must be carried out by students when going to the bathroom referring to the principles of fostering and environmental awareness culture. (2) The GETOL BERIMAN program to instill the character of caring for the environment is carried out during class hours with the procedure of raising hands, inviting friends and asking permission, bringing books and id cards, students going to the bathroom and friends as quality control, then checking books. (3) The supporting factors for this program are human resources, infrastructure and the inhibiting factor is the lack of student responsibility, program consistency.